2022
DOI: 10.1128/spectrum.00870-22
|View full text |Cite
|
Sign up to set email alerts
|

Human ACE2 Genetic Polymorphism Affecting SARS-CoV and SARS-CoV-2 Entry into Cells

Abstract: SARS-CoV and SARS-CoV-2 are known to cause severe pneumonia in humans. The S protein of these CoVs binds to the ACE2 molecule on the plasma membrane and mediates virus entry into cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…ACE2 is an important regulator of renin-angiotensin system that regulates blood pressure, fluid, and electrolyte balance, etc, and its polymorphism in humans has been discovered about 20 years ago [29,30] and has been linked to cardiovascular diseases, hypertension, and diabetic mellitus, etc [31][32][33]. Given that cardiovascular diseases, hypertension, and diabetic mellitus are important comorbidity factors for COVID-19, it is not surprising that recently the ACE2 polymorphism has also been found to not only be associated with entry efficiency of SARS-CoV-2 [34,35] but also with COVID-19 outcome [36], indicating that ACE2 polymorphism plays important roles in COVID pathogenesis. Many SARS-CoV related (SC1r-CoV) and SARS-CoV-2 related (SC2r-CoV) bat CoVs including RaTG13 also use human and bat ACE2 as the entry receptor [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 is an important regulator of renin-angiotensin system that regulates blood pressure, fluid, and electrolyte balance, etc, and its polymorphism in humans has been discovered about 20 years ago [29,30] and has been linked to cardiovascular diseases, hypertension, and diabetic mellitus, etc [31][32][33]. Given that cardiovascular diseases, hypertension, and diabetic mellitus are important comorbidity factors for COVID-19, it is not surprising that recently the ACE2 polymorphism has also been found to not only be associated with entry efficiency of SARS-CoV-2 [34,35] but also with COVID-19 outcome [36], indicating that ACE2 polymorphism plays important roles in COVID pathogenesis. Many SARS-CoV related (SC1r-CoV) and SARS-CoV-2 related (SC2r-CoV) bat CoVs including RaTG13 also use human and bat ACE2 as the entry receptor [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…However, this problem is beyond the scope of our review, and the reader can find relevant information in the recent review 312 and original papers. 186,193,[313][314][315] 5. Virus entry into human cells by binding to neuropilin-1 and other receptors ACE2 is widely recognized as the host cell receptor for SARS-CoV-2.…”
Section: Machine Learning and Alchemical Free Energy Methods For Pred...mentioning
confidence: 99%
“…However, this problem is beyond the scope of our review, and the reader can find relevant information in the recent review 312 and original papers. 186,193,313–315…”
Section: Interaction Of Sars-cov-2 Variants Of Concern With Ace2mentioning
confidence: 99%
“…Thus, individuals carrying these variant forms of ACE2 are predicted to be less susceptible to SARS-CoV-2 infection. Notably, the E 37 K polymorphism was found to decrease the ability of VSVDG*-SCoV-2 Beta (K 417 N/E 484 K-N 501 Y) to infect cells expressing such an ACE2 variant compared to the wild type ACE2 ( Hattori et al, 2022 ). In contrast, these authors found that two substitutions uncommon in the global population, H 505 R (MAF = 0.001%) and Y 515 C (MAF = 0.004%), enhanced the entry of Alpha and Delta (L 452 R-T 478 K) variants and the Delta variants respectively, compared to the wild type ACE2.…”
Section: Human Ace2 Polymorphism Supports the Hypothesis That The Ace...mentioning
confidence: 99%
“…Two ACE2 variants (E 35 K and F 72 V) possibly conferring resistance to the virus have higher allele frequencies in East Asian populations, while they have shown very low MAFs in European populations ( Chen et al, 2021 ). The E 35 K substitution, uncommon in the global population (MAF = 0.001%) but more frequently found in East Asian population (MAF = 0.01%) seems to be neutral for the entry of the SARS-CoV-2 Alpha variant but decreases the infectivity of the Beta (K 417 N/E 484 K-N 501 Y) variant ( Hattori et al, 2022 ). In the virus S protein, the apparent importance of K 417 and E 484 for interaction with ACE2 suggests the possibility that K 417 N and E 484 K substitutions should negatively affect binding to the ACE2 E 35 K mutant.…”
Section: Human Ace2 Polymorphism Supports the Hypothesis That The Ace...mentioning
confidence: 99%